Acoustic focusing through two layer annuluses in air - 管义钧 孙宏祥 刘树森 袁寿其 夏建平 葛勇 (Chinese physics B, 2016)
We report an acoustic focusing lens composed of two-layer annuluses made of metal cylinders in air. We find that the cylindrical waves can be focused into a perfect point without diffraction in the centre of the annuluses, which arises from the Mie-resonance modes in the annuluses. The focusing frequencies are related to the size of the inner annulus, and the focusing effect can be applied to the annuluses with different shapes and incident positions. Interesting applications of the focusing lens in the acoustic beam splitter and directional transmitter with energy enhancement are further discussed.